A Malignant Melanoma of the Penile : A Very Rare Case Report and Literature Review - Wijaya, Yanuar Hendra; Daniswara, Nanda; Santosa, Ardy; Soedarso, Mohamad Adi; Nugroho, Eriawan Agung; Addin, Sofyan Rais (RSUP Dr. Kariadi, 2021)
Background: Malignant melanoma of the penis is very rare, accounting for approximately 1.4% of all primary penile carcinomas. With a small prevalence of penile melanoma, there is lack of data about quality of the therapy. The primary treatment of melanoma of the penile is surgical, although there is a lack of consensus regarding the extent of treatment that is indicated. Case Report: A 60-year-old Caucasian man came to Division of Urology, Department of Surgery, Dr. Kariadi General Hospital Semarang with chief complaint painless and fast growing lesions on his penile. His general condition was fine, and has a normal vital signs. On the physical examination of penile region, there were found lesions on the ventral of the glans and penile foreskin and covered with blood and pus, with bilateral inguinal lymph nodes and lung metastasis from Multi Slice Computed Tomography. We already performed partial penectomy and bilateral inguinal lymph nodes dissection with histopathological results a malignant melanoma Clark IV. The final stage of penile melanoma was pT2N1M1. We follow-up the patient until 1 year after procedure, and there wasn’t any recurrence. Conclusion: Malignant melanoma of the penis is rare. Penile melanoma is highly treatable with surgical excision in its early stages because of resistant to both chemotherapy and radiotherapy. Delay in diagnosed and surgical treatment can lead to an adverse prognosis. The anamnesis, physical examination, and imaging studies must be done appropriately to improve the survival.